The Impact of Innovative Products in the Metallic Zinc Market Growth in Brazil - Nelson Roberto Furquim (FUCAPE Business School, 2017)
International market movements have been stimulating the recent process of industrialization in Brazil, with an increasing growth in the offer and demand of higher added value products in various sectors and segments. Metallic zinc plays a significant role in the Brazilian exports and in the automotive and building industries as well. Further to the availability of new technologies, the zinc industry in Brazil has been commercializing zinc alloys, perceived as higher added value products, for several applications. This study aims at analyzing how innovation and the zinc alloys may influence the metallic commodities market development in Brazil. It was carried a nationwide survey with a non-probabilistic sample of either employees or owners of companies that use zinc and its alloys. For the answers analysis it was used the Discourse of the Collective Subject, a qualitative and quantitative methodology. Zinc alloys influence positively the metallic zinc market growth, though their high prices were considered as a restriction factor for their use.